2017
DOI: 10.1038/s41598-017-07082-2
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral effects of γCdcPLI, a PLA2 inhibitor from Crotalus durissus collilineatus via PI3K/Akt pathway on MDA-MB-231 breast cancer cell

Abstract: Phospholipases A2 (PLA2s) overexpression is closely associated with the malignant potential of breast cancers. Here, we showed for the first the antitumoral effects of γCdcPLI, a PLA2 inhibitor from Crotalus durissus collilineatus via PI3K/Akt pathway on MDA-MB-231 cell. Firstly, γCdcPLI was more cytotoxic to MDA-MB-231 breast cancer cells than other cell lines (MCF-7, HeLa, PC3 and A549) and did not affect the viability of non-tumorigenic breast cell (MCF 10A). In addition, γCdcPLI induced modulation of impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 88 publications
(81 reference statements)
0
8
0
1
Order By: Relevance
“…The aortic ring assay is a well-accepted method for evaluating angiogenesis ( Gimenes et al, 2017 ; Weng et al, 2017 ): thoracic aortas were isolated, cut into rings, and used in the aortic ring assay as previously described. Microvessel sprouts began to merge at day 3 in aortic rings from mice treated with either NSD or HSD for consecutive 12 week.…”
Section: Resultsmentioning
confidence: 99%
“…The aortic ring assay is a well-accepted method for evaluating angiogenesis ( Gimenes et al, 2017 ; Weng et al, 2017 ): thoracic aortas were isolated, cut into rings, and used in the aortic ring assay as previously described. Microvessel sprouts began to merge at day 3 in aortic rings from mice treated with either NSD or HSD for consecutive 12 week.…”
Section: Resultsmentioning
confidence: 99%
“…Gimenes et al. reported that γCdcPLI1 inhibits the activity of PLA 2 in a PI3K/Akt dependent manner, possibly by interfering with the expression of Akt1/3 and PI3KR1 ( 68 ). Besides, PI3K also funds the activity of Crotoxin B, a catalytically active subunit IIA sPLA ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…These fragments were treated over 9 days, at 1-day intervals. Subsequently, the aortic rings were photographed using an inverted optical microscope (Nikon Eclipse TS100) [ 32 ] and the sprouting length was expressed in pixels for quantitative analysis in ImageJ software, as previously described by [ 33 ].…”
Section: Methodsmentioning
confidence: 99%